2023
DOI: 10.1002/cplu.202300112
|View full text |Cite
|
Sign up to set email alerts
|

Formate Over‐Oxidation Limits Industrialization of Glycerol Oxidation Paired with Carbon Dioxide Reduction to Formate

Abstract: Electrocatalytic CO 2 reduction processes are generally coupled with the oxidation of water. Process economics can greatly improve by replacing the water oxidation with a more valuable oxidation reaction, a process called paired electrolysis. Here we report the feasibility of pairing CO 2 reduction with the oxidation of glycerol on Ni 3 S 2 /NF anodes to produce formate at both anode and cathode. Initially we optimized the oxidation of glycerol to maximize the Faraday efficiency to formate by using design of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…In this way, coupling more valuable anodic reactions with CO 2 electroreduction has been the subject of recent and valuable contributions and has emerged as a promising approach to lower the overall cell voltage, and consequently the energy efficiency of the system, and also to simultaneously produce high-added-value products both at the cathode and anode. Among the different anodic processes used as paired reactions with CO 2 RR, the electrooxidation of glycerol (GOR, glycerol oxidation reaction) to high-added-value products is one of the most interesting alternatives. ,,,, Glycerol is the major waste product from biodiesel production and can be electrochemically oxidized into a variety of valuable chemicals. In this sense, Verma et al demonstrated that coupling CO 2 RR with the electrooxidation of glycerol reduced the power consumption of the system by 53% compared to use of the OER as anodic process. More recently, Junqueira et al reported the simultaneous production of formate both at the anode and cathode from the paired CO 2 RR and glycerol electrooxidation at high currents (200 mA cm 2 ) with FEs of about 96 and 45% at the anode and cathode, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, coupling more valuable anodic reactions with CO 2 electroreduction has been the subject of recent and valuable contributions and has emerged as a promising approach to lower the overall cell voltage, and consequently the energy efficiency of the system, and also to simultaneously produce high-added-value products both at the cathode and anode. Among the different anodic processes used as paired reactions with CO 2 RR, the electrooxidation of glycerol (GOR, glycerol oxidation reaction) to high-added-value products is one of the most interesting alternatives. ,,,, Glycerol is the major waste product from biodiesel production and can be electrochemically oxidized into a variety of valuable chemicals. In this sense, Verma et al demonstrated that coupling CO 2 RR with the electrooxidation of glycerol reduced the power consumption of the system by 53% compared to use of the OER as anodic process. More recently, Junqueira et al reported the simultaneous production of formate both at the anode and cathode from the paired CO 2 RR and glycerol electrooxidation at high currents (200 mA cm 2 ) with FEs of about 96 and 45% at the anode and cathode, respectively.…”
Section: Introductionmentioning
confidence: 99%